The Effect of Administering Ethanol Extract of Tempuyung Leaves(Sonchus arvensis L.) on Decreasing Uric Acid LevelsIn Mile Mice - Novidawati Boru Situmorang; Azahra Salsabila Mahriza (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: When serum uric acid levels are higher than normal, this condition is known as hyperuricemia. This condition is caused by increased breakdown of nucleic acids, decreased excretion, increased production of uric acid from purine-rich foods, or a combination of these. In traditional Indonesian medicine, tempuyung leaves (Sonchus arvensis L.) have traditionally been used to treat various diseases, including gout and kidney stones. Methods: Antihyperuricemic activity tests were conducted on 24 mice divided into six treatment groups. Hyperuricemia was induced by oral administration of chicken liver juice at a rate of 0.5 mL/20 gBW. Results: From days 1-6 after induction, uric acid levels in the test group increased progressively. In addition, the groups treated with allopurinol, 0.5% Na-CMC, and ethanol extract of tempuyung leaves (EEDT) at doses of 100, 300, and 500 mg/kgBW showed a decrease in uric acid levels on days 7 to 13. At doses of 500 mg/kgBW, 300 mg/kgBW, and 100 mg/kgBW, the allopurinol group experienced the greatest reduction, followed by the EEDT group. Conclusion: After allopurinol, the 500 mg/kgBW dose had the best antihyperuricemic efficacy, based on the percentage reduction in uric acid levels. Because the extract contains a large number of secondary metabolites, increasing the extract dose decreased the increase in effectiveness.